CURRENT ACCOUNT BALANCE AND ITS IMPLICATIONS FOR THE REAL EXCHANGE RATE IN PERU - Dávila Ángeles, Hugo Fuentes (2022)
The purpose of this study is to estimate the level of the underlying current account and normative current account for Peru and to analyze the implications on the equilibrium real exchange rate level derived by comparing both current account approaches. Among the most important results, we find current account levels below the equilibrium level during the 1998-2001 Russian crisis, the 2008-2009 financial crisis and the 2013-2015 period. Unlike the two periods of international crisis mentioned above, the years 2013-2015 did not see a significant reduction in GDP growth or a prolonged misalignment of the real exchange rate from its fundamentals.